Spatial and temporal variability of surface water and groundwater before and after the remediation of a Portuguese uranium mine area - Neiva, A.M.R. (2015)
The old Senhora das Fontes uranium mine, in central Portugal, consists of quartz veins which penetrated along fracture shear zones at the contact between graphite schist and orthogneiss. The mine was exploited underground until a depth of 90 m and was closed down in 1971. The ores from this mine and two others were treated in the mine area by the heap-leach process which ended in 1982. Seven dumps containing a total of about 33,800 m3 of material and partially covered by natural vegetation were left in the mine area. A remediation process took place from May 2010 to January 2011. The material deposited in dumps was relocated and covered with erosion resisting covers. Surface water and groundwater were collected in the wet season just before the remediation, in the following season at the beginning of the remediation and also after the remediation in the following dry season. Before, at the beginning and after the remediation, surface water and groundwater have an acid-to-alkaline pH, which decreased with the remediation, whereas Eh increased. In general, before the remediation, uranium concentration was up to 83 μg/L in surface water and up to 116 μg/L in groundwater, whereas at the beginning of the remediation it increases up to 183 μg/L and 272 μg/L in the former and the latter, respectively, due to the remobilization of mine dumps and pyrite and chalcopyrite exposures, responsible for the pH decrease. In general, after the remediation, the U concentration decreased significantly in surface water and groundwater at the north part of the mine area, but increased in both, particularly in the latter up to 774 μg/L in the south and southwest parts of this area, attributed to the remobilization of sulphides that caused mobilization of metals and arsenic which migrated to the groundwater flow. Uranium is adsorbed in clay minerals, but also in goethite as indicated by the geochemical modelling. After the remediation, the saturation indices of oxyhydroxides decrease as pH decreases. The remediation also caused decrease in Cd, Co, Cr, Ni, Pb, Zn, Cu, As, Sr and Mn concentrations of surface water and groundwater, particularly in the north part of the mine area, which is supported by the speciation modelling that shows the decrease of most dissolved bivalent species. However, in general, after the remediation, Th, Cd, Al, Li, Pb, Sr and As concentrations increased in groundwater and surface water at south and southwest of the mine area. Before and after the remediation, surface water and groundwater are contaminated in U, Cd, Cr, Al, Mn, Ni, Pb, Cu and As. Remediation caused only some improvement at north of the mine area, because at south and southwest part, after the remediation, the groundwater is more contaminated than before the remediation.